a) 27дм 4см + 5м 62 см = 8м 3дм 6 см
б) 9м 6см - 32дм 5см = 5м 8дм 1 см
Пошаговое объяснение:
a) 27дм 4см + 5м 62 см = 2м 74см + 5м 62см = 274 см + 562 см = 836 см = 8м 3дм 6 см
б) 9м 6см - 32дм 5см = 90дм 6см - 32дм 5см = 906 см - 325 см = 581 см = 5м 8дм 1 см
a) 27дм 4см + 5м 62 см = 8м 3дм 6 см
б) 9м 6см - 32дм 5см = 5м 8дм 1 см
Пошаговое объяснение:
a) 27дм 4см + 5м 62 см = 2м 74см + 5м 62см = 274 см + 562 см = 836 см = 8м 3дм 6 см
б) 9м 6см - 32дм 5см = 90дм 6см - 32дм 5см = 906 см - 325 см = 581 см = 5м 8дм 1 см